Joint RREPS-13 (X International Symposium on Radiation from Relativistic Electrons in Periodic Structures) and Meghri-13 (Electron, Positron, Neutron and X-ray Scattering under External Influences) Lake Sevan, Armenia, 23-28 September 2013 - Potylitsyn Russian physicist Professor of the TPU; Karataev physicist head of the laboratory of Tomsk Polytechnic University; Mkrtchyan (Journal of Physics: Conference Series, 2014)
Published under licence in Journal of Physics: Conference Series by IOP Publishing Ltd. All rights reserved. No part of this publication may be reproduced, stored in a retrieval system or transmitted in any form or by any means, electronic, mechanical, photocopying, recording or otherwise, without the written permission of the publisher, except as stated below. Single photocopies of single articles may be made for private study or research. Illustrations and short extracts from the text of individual contributions may be copied provided that the source is acknowledged, the permission of the authors is obtained and IOP Publishing Ltd is notified. Multiple copying is permitted in accordance with the terms of licences issued by the Copyright Licensing Agency under the terms of its agreement with the Committee of Vice-Chancellors and Principals. Authorization to photocopy items for internal or personal use, or the internal or personal use of specific clients in the USA, is granted by IOP Publishing Ltd to libraries and other users registered with the Copyright Clearance Center (CCC) Transactional Reporting Service, provided that the base fee of $33.00 per copy is paid directly to CCC, 222 Rosewood Drive, Danvers, MA 01923, USA.